TINGKAT PENGETAHUAN DAN SIKAP PRIA REMAJA AKHIR TENTANG DISPEPSIA AKIBAT KOPI DI FAKULTAS TEKNIK SIPIL UNIVERSITAS ABULYATAMA - Zurryani Zurryani; Said Aandi Saida (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Background: One of the risk factors of dyspepsia are consuming excessive coffee. In coffee contains caffeine that can increase stomach acid so irritate the gastric mucosa. Knowledge and attitudes about coffee-induced dyspepsia also have an effect on the occurrence of dyspepsia. Research purposes: To know the level of knowledge and attitude of late adolescent man about coffee dyspepsia. Methods: This study is descriptive with cross sectional study conducted in Marchand July with a sample of 62 students late teens Abulyatama Force Civil Engineering University, 2016. The sampling technique in this research huse accidental sampling. The data were collected from the research sample using questionnaire. Results: In general, the results showed that a good knowledge that is 66.1% and the poor is 33.9% of the 62 respondents, showed good attitude that is 64.5% and poor 35.5% of 62 respondents. While from 62 respondent’s positive dyspepsia is37.1% and negative dyspepsia 62.9%. Conclusion: Based on the above it can be concluded that the knowledge and attitudes of teenage boys final at the Faculty of Civil Engineering University Abulyatama mostly good.And found a small percentage of respondents whopositive dyspepsia.Keywords: Attitude, coffe, dyspepsia, knowledge